Golabi-Ito-Hall syndrome results from a missense mutation in the WW domain of the PQBP1 gene. Issue 6 (1st June 2006) - Lubs, H; Abidi, F E; Echeverri, R; Holloway, L; Meindl, A; Stevenson, R E; Schwartz, C E
Abstract : Background: Golabi, Ito, and Hall reported a family with X linked mental retardation (XLMR), microcephaly, postnatal growth deficiency, and other anomalies, including atrial septal defect, in 1984. Methods: This family was restudied as part of our ongoing study of XLMR, but significant linkage to X chromosome markers could not be found. Extreme short stature and microcephaly as well as other new clinical findings were observed. Mutations in the polyglutamine tract binding protein 1 gene ( PQBP1 ) have recently been reported in four XLMR disorders (Renpenning, Hamel cerebro-palato-cardiac, Sutherland-Haan, and Porteous syndromes) as well as in several other families. The clinical similarity of our family to these patients with mutations in PQBP1, particularly the presence of microcephaly, short stature, and atrial septal defect, prompted examination of this gene. Results: A missense mutation in PQBP1 was identified which changed the conserved tyrosine residue in the WW domain at position 65 to a cysteine (p.Y65C). Conclusions: This is the first missense mutation identified in PQBP1 and the first mutation in the WW domain of the gene. The WW domain has been shown to play an important role in the regulation of transcription by interacting with the PPxY motif found in transcription factors. The p.Y65C mutation may affect the proper functioning of the PQBP1 protein as a transcriptional co-activator.